Artificial intelligence, cartoons, and mathematics: reflections on classroom organization in fiction and reality (Edma 0-6: Educación Matemática en la Infancia, 2024)
In this article, we explore how the aspect of a Mathematics classroom is reflected in fiction, especially in cartoons. We analyze scenes from the film "Leo" and other productions that depict a traditional classroom layout, reflecting on its impact on mathematical activity. We highlight the importance of classroom layout and teacher management in the development of mathematical processes such as communication and representation. Additionally, we investigate the bias in images generated by artificial intelligence (AI), which reflect stereotypes similar to those in fiction. Finally, we contrast these setups with Liljedahl's proposal to foster a culture of mathematical thinking and communication.
Keywords: artificial intelligence; cartoons; mathematics education; early childhood education; classroom organization